Intonation patterns : an analysis of EFL learners’ interlanguage at university level - Aguirre Sotelo, Evangelina (2019)
The present study intends to examine tone selection to signal information status by undergraduate students of English as a foreign language (EFL) in the Phonetics and Phonology I course at the School of Languages, Universidad Nacional de Córdoba. This analysis, which is mainly perceptual but also supported acoustically, aims to detect the most common problems in the use of intonation contours of a group of EFL learners and to describe these learners’ IL phonology.